Gender, Creativity and Education in Digital Musics and Sound Art. Issue 1 (2nd January 2016) - Born, Georgina; Devine, Kyle
Abstract : This special issue examines the politics of gender in relation to higher education, creative practices and historical processes in electronic music, computer music and sound art. The starting point is a summary of research findings on the student demographics associated with the burgeoning of music technology (MT) undergraduate degrees in Britain since the mid-1990s. The findings show a clear bifurcation: the demographics of students taking British MT degrees, in comparison to traditional music degrees and the national average, are overwhelmingly male, from less advantaged social backgrounds, and slightly more ethnically diverse. At issue is the emergence of a highly (male) gendered digital music field. The special issue sets these findings into dialogue with papers by practitioners and scholars concerned with gender in relation to educational, creative and historical processes. Questions addressed include: What steps might be taken to redress gender inequalities in education, and in creative, compositional and curatorial practices? How can we combat the tendency to focus exclusively on the 'problem of women' while at the same time ignoring the challenges posed by the marked styles of masculinity evident in these fields? Is the gendering of electronic and digital musics and sound art evident in certain aesthetic directions? And what musical futures are augured by such imbalances?